ECONOMETRIC MODELLING OF THE INNOVATION PROCESS IN UZBEKISTAN - Saidova Marhabo Xabibullo daughter (American Journals Publishing, 2023)
This paper is dedicated to the analysis of factors affecting innovation in Uzbekistan taking the case of the Joint Stock Company “Uzkimyosanoat”. It involved obtaining primary data for 10 enterprises in the company and analyzing this data. Factors to be looked at were chosen as research and development, intellectual knowledge, human abilities, level of satisfaction, demand for changes, usage of ICT and product development, growth of enterprise.
Keywords: Innovation, variables, econometric model, factor, enterprise.